Stronger together. (2nd December 2019) - Ellwood, Fiona; Deverick, Julie; Rochford, Diane; McGovern, Debbie; Hemington, Debbie; Martin, Dave; Johnson, Andrea
Abstract : Collaborative practice is key to achieving optimal outcomes and is widely considered the blueprint for the future of healthcare. We hear from some key dental care professionals on why they believe in the importance of forging bonds across the dentistry workforce